2022
DOI: 10.1108/ijwhm-09-2021-0179
|View full text |Cite
|
Sign up to set email alerts
|

Organizational support and perceived environment impact on quality of care and job satisfaction: a study with Pakistani nurses

Abstract: PurposeReferring to the theory of organizational empowerment, the purpose of this study is to examine the relationship of organizational support and perceived environment on quality of care and job satisfaction, with organizational commitment as a mediator for the first variable.Design/methodology/approachThis study employed a cross-sectional research design and data was collected from seven private and public sector hospitals in Pakistan, involving 352 nurses on a voluntary basis through a self-administered s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 93 publications
0
8
0
Order By: Relevance
“…Ultimately, we reiterate that these two investigations contribute substantially to our general understanding of workplace health management, an area of research that has placed a considerable amount of effort on procuring the betterment of members' wellbeing experiences (e.g. Ahmad et al ., 2022; Hemming et al ., 2021; Khan et al ., 2022; Rhodes et al ., 2022). Moreover, the implications of these findings and contributions are manifold.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…Ultimately, we reiterate that these two investigations contribute substantially to our general understanding of workplace health management, an area of research that has placed a considerable amount of effort on procuring the betterment of members' wellbeing experiences (e.g. Ahmad et al ., 2022; Hemming et al ., 2021; Khan et al ., 2022; Rhodes et al ., 2022). Moreover, the implications of these findings and contributions are manifold.…”
Section: Discussionmentioning
confidence: 96%
“…Finally, this work will contribute substantially to the arena of workplace health management (e.g. Ahmad et al ., 2022; Hemming et al ., 2021; Khan et al ., 2022; Rhodes et al ., 2022). Indeed, such information will be of decided value to organizational scholars that investigate relational dynamics in the workplace (e.g.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Their CA is crucial for attracting the abilities, information, and intelligence of the school community. Likewise, another study showed on 352 nurses establishes that OC facilitated the relationship b/t organizational support and JS with the quality of care delivered and that, the observed work setting was found to have an influence on JS and the quality of care (Ahmad et al, 2022). In general, the literature advises that age, gender, education level, and years of work experience have revealed important relationships with CA in some studies, while in others, these factors did not show significant relationships.…”
Section: Commitment Ability (Ca)mentioning
confidence: 94%
“…Their experiments revealed that nurses’ job burnout was related to a series of factors, such as structural empowerment, real leadership ability, and work-life interference. For organizational employees, fairness, supervisor support, organizational rewards, and favorable working conditions are related to building a strong sense of organizational support, and these are conducive to improving and increasing job satisfaction and positive emotions ( Rhoades and Eisenberger, 2002 ; Ahmad et al, 2022 ). Some previous studies ( Liu et al, 2018 ) indicated that organizational support can predict nurses’ turnover intention, and it plays a mediating role between their job satisfaction and job burnout.…”
Section: Introductionmentioning
confidence: 99%